Low-temperature internal quantum efficiency of GaInN/GaN quantum wells under steady-state conditions. (31st January 2022) - Sidikejiang, Shawutijiang; Henning, Philipp; Horenburg, Philipp; Bremers, Heiko; Rossow, Uwe; Menzel, Dirk; Hangleiter, Andreas
Abstract: We compare the low-temperature photoluminescence (PL) intensities of a range of GaInN/GaN quantum well (QW) structures under identical excitation conditions, mounting the samples side by side. Normalizing the measured intensity to the absorbed power density in the QWs, we find that low-temperature PL efficiencies of several samples, which show close to 100% internal quantum efficiency (IQE) in time-resolved PL, saturate at nearly an identical value. Of course, this is strong indicative of being 100% IQE at low temperature for those efficient samples. Using the low-temperature PL efficiency as a 'Reference', on the other hand, we observe not only the effects of temperature-independent non-radiative losses on the low-temperature IQE, but also are able to determine the IQE of arbitrary samples on an absolute scale. Furthermore, we prove the experimental results by comparing the low-temperature efficiencies of a sample with an initial 100% IQE after intentionally introducing structural defects with argon-implantation.